Reduced Interface‐Mediated Recombination for High Open‐Circuit Voltages in CH3NH3PbI3 Solar Cells. Issue 28 (26th May 2017) - Wolff, Christian M.; Zu, Fengshuo; Paulke, Andreas; Toro, Lorena Perdigón; Koch, Norbert; Neher, Dieter
Abstract : Perovskite solar cells with all‐organic transport layers exhibit efficiencies rivaling their counterparts that employ inorganic transport layers, while avoiding high‐temperature processing. Herein, it is investigated how the choice of the fullerene derivative employed in the electron‐transporting layer of inverted perovskite cells affects the open‐circuit voltage ( V OC ). It is shown that nonradiative recombination mediated by the electron‐transporting layer is the limiting factor for the V OC in the cells. By inserting an ultrathin layer of an insulating polymer between the active CH3 NH3 PbI3 perovskite and the fullerene, an external radiative efficiency of up to 0.3%, a V OC as high as 1.16 V, and a power conversion efficiency of 19.4% are realized. The results show that the reduction of nonradiative recombination due to charge‐blocking at the perovskite/organic interface is more important than proper level alignment in the search for ideal selective contacts toward high V OC and efficiency. Abstract : Perovskite solar cells have emerged as one of the most promising solar‐cell technologies for the next generation of photovoltaics. Despite simple and cheap processing, the solar cells exhibit comparably little loss in open‐circuit voltage. An approach to further reduce this loss by optimizing the charge selectivity of the fullerene‐based electron contact in efficient devices is shown.